Advancing Soft Tissue Reconstruction with a Ready-to-Use Human Adipose Allograft - Victor Fanniel; Ihab Atawneh; Jonathan Savoie; Michelle Izaguirre-Ramirez; Joanna Marquez; Christopher Khorsandi; Shauna Hill (Bioengineering, 2025)
Soft tissue reconstruction remains a challenge in clinical practice, particularly for restoring substantial volume loss due to surgical resections or contour deformities. Current methods, such as autologous fat transplantation, have limitations, including donor site morbidity and insufficient tissue availability, necessitating an innovative approach. This study characterizes alloClae, a minimally manipulated human-derived adipose allograft prepared using a detergent-based protocol to reduce DNA content while preserving adipose tissue structure. Proteomic analysis revealed that alloClae retains key native proteins critical for graft integration with the host and stability, with key extracellular matrix (ECM) components, collagens, elastins, and laminin, which are more concentrated as a result of the detergent-based protocol. Biocompatibility of alloClae was assessed in vitro using cytotoxicity and cell viability assays in fibroblast cultures, revealing no adverse effects on cell viability, membrane integrity, or oxidative stress. Additionally, in vitro studies with adipose-derived stem cells (ASCs) demonstrated attachment and differentiation, with lipid droplet accumulation observed by day 14, indicating support for adipogenesis. A 6-month longitudinal study in athymic mice showed stable graft retention, host cell infiltration, and formation of new adipocytes and vasculature within alloClae by 3 months. The findings highlight alloClae’s ability to support host-driven adipogenesis and angiogenesis while maintaining graft stability throughout the study period. It presents a promising alternative to the existing graft materials, offering a clinically translatable solution for soft tissue reconstruction.